2015
DOI: 10.1186/s12916-015-0376-6
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of individual patient data meta-analyses in orthopaedic surgery

Abstract: BackgroundThe number of individual patient data meta-analyses published is very low especially in surgical domains. Our aim was to assess the feasibility of individual patient data (IPD) meta-analyses in orthopaedic surgery by determining whether trialists agree to send IPD for eligible trials.MethodsWe performed a literature search to identify relevant research questions in orthopaedic surgery. For each question, we developed a protocol synopsis for an IPD meta-analysis and identified all related randomized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 35 publications
(35 reference statements)
1
21
0
Order By: Relevance
“…The current study resulted in a low obtainment of IPD for this exercise meta-analysis, with less than one-third of eligible studies providing IPD. The response rates observed are either similar to [ 10 , 42 ], lower than, [ 9 , 43 ] or higher [ 44 ] than previous research across a variety of different subject areas. While one might speculate that the formation of a consortium could have increased the response rate, a previous IPD meta-analysis on obesity and diabetes was only able to retrieve approximately 40% of IPD when such a consortium was established [ 42 ].…”
Section: Discussionsupporting
confidence: 59%
“…The current study resulted in a low obtainment of IPD for this exercise meta-analysis, with less than one-third of eligible studies providing IPD. The response rates observed are either similar to [ 10 , 42 ], lower than, [ 9 , 43 ] or higher [ 44 ] than previous research across a variety of different subject areas. While one might speculate that the formation of a consortium could have increased the response rate, a previous IPD meta-analysis on obesity and diabetes was only able to retrieve approximately 40% of IPD when such a consortium was established [ 42 ].…”
Section: Discussionsupporting
confidence: 59%
“…We also found that the Bayesian IPD-NMAs were more likely to use the 1-stage process, and the Frequentist IPD-NMAs were more likely to use the 2-stage process. Reluctance to share data is a major obstacle to obtaining IPD and performing IPD meta-analysis [36,37]. A previous study showed that IPD sharing may depend on study characteristics, including funding type, study size, study risk of bias, and treatment effect [27].…”
Section: Findings and Interpretationsmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26][27][28][29][30][31] However, it has been suggested that reluctance to share data is still the main obstacle for obtaining IPD and performing IPD metaanalysis. [32,33] Potential reasons for this include concerns about patient confidentiality, lack of time to share IPD, not 'owning' the data, cost for de-identifying and formatting the data, or M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 6 lack of access to data by primary study authors after study completion. [32] A scoping review of indirect comparisons with IPD showed that 67% of included studies obtained IPD through the establishment of a collaborative group.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…[32,33] Potential reasons for this include concerns about patient confidentiality, lack of time to share IPD, not 'owning' the data, cost for de-identifying and formatting the data, or M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 6 lack of access to data by primary study authors after study completion. [32] A scoping review of indirect comparisons with IPD showed that 67% of included studies obtained IPD through the establishment of a collaborative group. [8] Hence, the cooperation of the authors of the primary studies is crucial for providing IPD in a usable format and answering queries about their data.…”
Section: A N U S C R I P Tmentioning
confidence: 99%